Mungkinkah Dual Belonging sebagai Alternatif Mencapai Kesempurnaan Rohani? Sebuah Survey Awal - Bedali Hulu (Indonesian Journal of Theology, 2022)
Dual belonging emerges as a societal reality shaped by the formations of certain social and cultural interactions and family systems. As the works of Paul F. Knitter, Rose Drew, and Catherine Cornille show, the reality of dual belonging is in practice nothing new, particularly in Asia—including Indonesia. By means of their personal encounters vis-à-vis the reality of a religious diversity that is deeply integrated in social and cultural life (specifically in Asia), the contributions of Knitter, Drew, and Cornille prove both valuable for building interreligious dialogue and cooperation as well as beneficial for spiritual growth. Knitter and Drew, for instance, regard dual belonging as a societal good and positive merit of tradition, with Knitter even concluding that dual belonging presents a worthwhile alternative for making spiritual progress. Although Cornille mostly agrees that the ritual practices associated with dual belonging may offer spiritual benefits, she is dubious about the commitment and personal conviction of anyone who simultaneously pursues dual belonging in practice—though this clearly relates to Cornille’s position on multiple religious identification. While the practical development of dual belonging raises doubts and tension among adherents of variegated religions, the practice of dual belonging has become a sociocultural good within Asian tradition even despite the tension it brings, and this includes the case of Indonesia (Albertus Bagus Laksana). Dual belonging practices, such as pilgrimage in Indonesia, can nevertheless be beneficial for one’s spiritual growth when that spirituality is rooted in one’s religious beliefs. This article affirms the acceptability of dual belonging at the level of religious experience while also granting that claims of particularity on a cognitive level remain difficult to bridge.